The Treatment of Cartilage Damage Using Human Mesenchymal Stem Cell-Derived Extracellular Vesicles: A Systematic Review of in vivo Studies - To, Kendrick; Romain, Karl; Mak, Christopher; Kamaraj, Achi; Henson, Frances; Khan, Wasim (Frontiers in Bioengineering and Biotechnology, 2020)
Damage to joints through injury or disease can result in cartilage loss, which if left untreated can lead to inflammation and ultimately osteoarthritis. There is currently no cure for osteoarthritis and management focusses on symptom control. End-stage osteoarthritis can be debilitating and ultimately requires joint replacement in order to maintain function. Therefore, there is growing interest in innovative therapies for cartilage repair. In this systematic literature review, we sought to explore the in vivo evidence for the use of human Mesenchymal Stem Cell-derived Extracellular Vesicles (MSC-EVs) for treating cartilage damage. We conducted a systematic literature review in accordance with the PRISMA protocol on the evidence for the treatment of cartilage damage using human MSC-EVs. Studies examining in vivo models of cartilage damage were included. A risk of bias analysis of the studies was conducted using the SYRCLE tool. Ten case-control studies were identified in our review, including a total of 159 murine subjects. MSC-EVs were harvested from a variety of human tissues. Five studies induced osteoarthritis, including cartilage loss through surgical joint destabilisation, two studies directly created osteochondral lesions and three studies used collagenase to cause cartilage loss. All studies in this review reported reduced cartilage loss following treatment with MSC-EVs, and without significant complications. We conclude that transplantation of MSC-derived EVs into damaged cartilage can effectively reduce cartilage loss in murine models of cartilage injury. Additional randomised studies in animal models that recapitulates human osteoarthritis will be necessary in order to establish findings that inform clinical safety in humans.